2021
DOI: 10.3390/ma14040752
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Hardened 3D Printed Concretes and Mortars—Development of a Consistent Experimental Characterization Strategy

Abstract: Today, it is already foreseeable that additive manufacturing of mortar and concrete has groundbreaking potential and will revolutionize or at least fundamentally change the way we build. In recent years, 3D concrete printing (3DCP) with extrusion-based deposition methods has been pushed forward by a growing research community. Albeit being regarded one of the most promising innovations in construction industry, a consistent characterization methodology for assessing the constitutive behavior of 3D printed, har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 38 publications
1
12
0
2
Order By: Relevance
“…While it was understood that the perpendicular and parallel directions were similar at a rate of 33%, it was understood that the loads applied in the perpendicular and lateral directions at a rate of 33% gave similar strength. As a result, as stated by Bong et al, 56 and Meurer et al, 60 it was observed that parallel and lateral loadings had the highest similar strength compared to other combinations.…”
Section: Hardened State Properties Of 3dpc Mixturessupporting
confidence: 56%
“…While it was understood that the perpendicular and parallel directions were similar at a rate of 33%, it was understood that the loads applied in the perpendicular and lateral directions at a rate of 33% gave similar strength. As a result, as stated by Bong et al, 56 and Meurer et al, 60 it was observed that parallel and lateral loadings had the highest similar strength compared to other combinations.…”
Section: Hardened State Properties Of 3dpc Mixturessupporting
confidence: 56%
“…Two mixings and two 3D printing tests were carried out separately in the same order. This is because the mechanical properties of 3DCP can be influenced by the age of the fresh mortar mixture [ 19 ]. After mixing each mortar, the slump flow test of ASTM C1437 [ 23 ] was performed immediately after mixing and at the start of 3D printing to measure the consistency of the mortar mixture.…”
Section: Methodsmentioning
confidence: 99%
“…However, the performance of hardened concrete varies depending on the method used to make the test specimen, test method and condition, specimen size, etc. [ 19 ]. Furthermore, there is still no standard for evaluating and judging the material requirements and characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Mortar mixes based on the mixture proportions in Table 3 were used and printed using the 3DCP system similarly and in the same order in all six types of print tests. This reduced the change in the mechanical properties of 3DCP by the age of the mix material as much as possible [31]. After mixing each mortar, a slump-flow test according to ASTM C1437 was performed twice using the mortar immediately after the end of mixing and the first printed mortar to measure consistency [32].…”
Section: Printing Materialsmentioning
confidence: 99%